Study on resting-state functional connectivity characteristics under hypnosis using functional near-infrared spectroscopy - Zhang, Zhisong; Tan, Wanqiu; Ma, Yuhong; Zheng, Min; Zhang, Yuan; Wei, Jiaming; Wang, Yaozu; Li, Zhimeng; Li, Zhifei; Ho, Roger C. (Frontiers in Psychology, 2025)
ObjectiveNumerous studies suggest that hypnosis has significant potential in mental health and cognitive disorder treatments. However, the mechanisms by which hypnosis influences brain activity and functional network connectivity remain unclear. This study employed functional near-infrared spectroscopy (fNIRS) to investigate resting-state functional connectivity (rsFC) under hypnosis.MethodsTwenty-six healthy college students participated in the study. Resting-state oxygenated hemoglobin (HbO) data were collected from the prefrontal cortex (PFC) during both control aware and hypnotic states. Functional connectivity strengths between these states were analyzed to assess changes in brain activity associated with deep hypnosis.ResultsA total of 55 paired samples t-tests were conducted across 11 regions of interest (ROIs), revealing statistically significant differences (p < 0.05) in functional connectivity strength between the control state and hypnotic state in 10 paired comparisons. Increased connectivity during hypnosis (6 pairs): LBA9-RBA10 (t = −2.672, p = 0.013), LBA6-RBA46 (t = −2.948, p = 0.007), LBA46-RBA46 (t = −2.516, p = 0.019), RBA8-RBA46 (t = −2.689, p = 0.013), RBA9-RBA46 (t = −2.090, p = 0.047), LBA10-RBA10 (t = −2.315, p = 0.029); Decreased connectivity during hypnosis (4 pairs): LBA9-LBA45 (t = 2.064, p = 0.049), LBA6-LBA45 (t = 3.151, p = 0.004), LBA8-LBA45 (t = 2.438, p = 0.022), LBA8-RBA9 (t = 2.085, p = 0.047). No significant differences were observed in connectivity strength between other ROI pairs.ConclusionHypnosis appears to modulate the function of the DLPFC, PFC, and related regions, enhancing specific brain network functional connectivity. This preliminary study demonstrates that resting-state functional connectivity analysis using fNIRS is a valuable approach for studying brain activity during hypnosis.